2021
DOI: 10.1021/acscatal.1c04583
|View full text |Cite
|
Sign up to set email alerts
|

Rerouting the Organocatalytic Benzoin Reaction toward Aldehyde Deuteration

Abstract: Reactive intermediates are key to halting and promoting chemical transformations; however, due to their elusive nature, they are not straightforwardly harnessed for reaction design. Herein, we describe studies aimed at stabilizing reactive intermediates in the N-heterocyclic carbene (NHC) catalytic cycle, which enabled the full shutdown of the known benzoin coupling pathway, while rerouting its intermediates toward deuteration. The reversible nature of NHC catalysis and the selective stabilization of reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…N-Heterocyclic carbenes (NHCs) are the most studied family of nucleophilic carbenes. [1][2][3][4][5][6][7][8][9] They are generally well known as excellent nitrogen ligands for transition metal-based catalysis, [10][11][12][13][14][15][16][17] various types of carbon-carbon (C-C), carbon-halogen (C-X) and carbon-heteroatom (C-HA) mediated cross-coupling reaction, [18][19][20] and olefin metathesis, [21][22][23][24][25] but there is growing interest in the role of nucleophilic carbenes in field of organocatalytic reactions. [26][27][28][29][30][31] Metal-free organocatalytic processes are more interesting alternatives to classical organic transformations method since they are often more economical, most of the catalytic systems possibly recover back active catalyst with good turnover rate, less air-sensitive NHC-salts and non-toxic reagents.…”
Section: Introductionmentioning
confidence: 99%
“…N-Heterocyclic carbenes (NHCs) are the most studied family of nucleophilic carbenes. [1][2][3][4][5][6][7][8][9] They are generally well known as excellent nitrogen ligands for transition metal-based catalysis, [10][11][12][13][14][15][16][17] various types of carbon-carbon (C-C), carbon-halogen (C-X) and carbon-heteroatom (C-HA) mediated cross-coupling reaction, [18][19][20] and olefin metathesis, [21][22][23][24][25] but there is growing interest in the role of nucleophilic carbenes in field of organocatalytic reactions. [26][27][28][29][30][31] Metal-free organocatalytic processes are more interesting alternatives to classical organic transformations method since they are often more economical, most of the catalytic systems possibly recover back active catalyst with good turnover rate, less air-sensitive NHC-salts and non-toxic reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we exploit recent NHC catalysis studies and mechanistic insights on the stabilization of such reactive intermediates for the selective deuteration of aromatic, alkene and alkyl aldehydes. We showed that intercepting a stabilized reactive aldehyde intermediate can work as a facile starting point to introduce the deuterium Isotope labeling and eliminating the generation of classical homo‐benzoin by‐product [30–31] …”
Section: Introductionmentioning
confidence: 99%
“…The high transition state results from a highly strained three-membered ring, which almost requires the complete breaking of the C–H bond before forming the O–H one . Consequently, it was shown that a base (such as DBU or K 2 CO 3 ), water- or alcohol-assisted HAT is a much more plausible alternative. …”
mentioning
confidence: 99%
“…Since we can guesstimate that normally accessible dried solvents can still have a water content of the order of millimolar, it is clear that water-assisted HAT is the preferred mechanism. It is possible that a two-water-molecule mechanism can also participate at high concentration (we estimate more than millimolar concentration to make this pathway relevant), , an effect that we will study in the future.…”
mentioning
confidence: 99%
See 1 more Smart Citation